Refinement of Southern white rhinoceros semen sample processing protocols to optimize post-thaw sperm viability and integrity - Ferreira, Jana (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.